A Study on Consumer Behavior Towards Online Shopping with Special Reference to Age Group - Ms. Mariyam Ahmed, Ms. Jasmine Joshi (Mathematical Statistician and Engineering Applications, 2022)
With increasing population the demand for quality product and advancement of technology is also increasing. This results in the gravitation towards the comfort of buying and selling product in just a click. In this fast moving world where earning becomes top most priority, the needs and wants have taken a backseat. To understand this gap of transition from the offline to online mode, we have conducted this study on the buying behavior towards online shopping specially taking the age factor as the dependent variable. The buying pattern and curiosity is changed according to the age and we have proved it with the help of percentage analysis. A sample size of 50 is selected in random mode and we have done the survey by circulating questionnaire with reference to branding, age, gender and buying pattern. The qualitative and quantitative study is done and at the end we have concluded our finding with the solution that we think is required to understand this transition towards online mode and why certain age group of people are more drawn towards it.